Effect of Codonopsis pilosula Polysaccharides on the Growth and Motility of Hepatocellular Carcinoma HepG2 Cells by Regulating β-Catenin/TCF4 Pathway - Yuan-yuan Zhang; Ying-mei Zhang; Hai-yan Xu (International Journal of Polymer Science)
Objective. To study the effect of Codonopsis pilosula polysaccharide (CPP) on the growth and motility of HepG2 cells and its possible mechanism. Methods. Cells were randomly divided into Control group, CPP (5 μM) group, CPP (10 μM) group, and CPP (20 μM) group. The proliferation, invasion, migration ability, and expression of proteins involved in the epithelial-mesenchymal transition (EMT) and signaling pathway of HepG2 cells were detected by CCK8 assay, BrdU staining, Transwell, Scratch test, and Western blot, respectively. Results. Codonopsis pilosula polysaccharide inhibited the proliferation of HepG2 cells cultured in vitro along with the expression level of Ki67 and PCNA protein (P<0.05), decreased the number of invasive cells (P<0.05), and reduced the scratch closure rate (P<0.05). It also adjusted the expression of vascular endothelial growth factor (VEGF), E-cadherin, and N-cadherin (P<0.05). Other than that, downregulation of β-catenin, TCF4, and c-Myc protein expression (P<0.05) was observed as well. Conclusion. Codonopsis pilosula polysaccharide can inhibit the proliferation and motility of HepG2 cells cultured in vitro, and the underlying mechanism is proposed to be related to the inhibition of the β-catenin/TCF4 pathway.